Customer Response towards Funding Return Uncertainty in Indonesian Islamic Banking - Nur Fatoni; Mustaqim Pabbajah (Shirkah: Journal of Economics and Business, 2024)
A guaranteed return on funding is the expectation of customers when engaging in transactions with Islamic banks, yet it remains uncertain. This study aims to explain customer responses to the uncertainty of funding returns in Islamic Banks in Indonesia. The research is based on descriptive qualitative methods, with data collected through observations and interviews. Observations involved visiting bank branches and interacting with employees to explain the research intent. The researchers directly observed funding transactions at several selected Islamic banks in Semarang municipality, Indonesia. Interviews were conducted with customers from these banks, selecting at least one funding customer for each interview (N= 4). Data were analyzed using descriptive analysis methods. The study found that the uncertainty of funding returns is attributed to the application of the mudharabah contract. Customers are not overly concerned with the return uncertainty as long as the Islamic bank operates normally. Loyal customers prefer Islamic banks for their funds placement, considering the total return competitive. This research refutes the perception among some in the public that Islamic banks are similar to conventional banks. Islamic banks must maintain competitive equivalent rates to preserve customer loyalty.Â